(untitled) (Journal of Hama University, 2020)
The aim of this study was to determine the type of mesiobuccal root morphology and the prevalence of second mesiobuccal canal in maxillary first molars. Sample size consisted of 90 upper first molars freshly extracted and were randomly enrolled into three groups as following: (Naked eye examination [group1]), (Microscope examination [group 2]) and (CBCT examination [group 3]). Then, sample was made transparent after ensuring that both MB1 and MB2 were recapitulated with K-file #10 toward the apex. This study showed that the overall frequency of MB2 in maxillary first molars in three groups is 93.33%. However, the frequency of MB2 when examined using microscope (68.49%) and CBCT (73.91%) was higher than Naked eye examination (18.89%). Also results showed that the frequency of type I of MB1 and MB2 (52.38%) was higher than the frequency of type II (22.62%) and type IV (25%).Conclusion: The accurate The method the higher the chance of finding second mesiobuccal canal. Thus, is preferred to use multiple examination methods to detect MB2 so it can be probably shaped to obtain a sufficient and complete sealing for the root canal system.